AKTIVITAS ANTIOKSIDAN HIDROLISAT PROTEIN IKAN WADER (Rasbora jacobsoni) DARI HIDROLISIS OLEH ENZIM CALOTROPIN DAN PAPAIN - Yuli Witono; Maryanto Maryanto; Iwan Taruna; Ardiyan Dwi Masahid; Kinanti Cahyaningati (JURNAL AGROTEKNOLOGI, 2020)
The potency of common barb fish as fish protein hydrolyzate caused by its high protein content. Fish protein hydrolyzate is produced through the hydrolysis process by the calotropin enzyme and the papain enzyme. This study used common barb fish with one type of treatment, i.e. the difference combination of the calotropin (C) and papain (P) enzyme. Making fish protein hydrolyzate is used to determine the antioxidant activity of the common barb fish protein hydrolyzate. The observation parameters in this study were enzyme activity, antioxidant activity, degree of hydrolysis, molecular weight, amino acids, dissolved protein content, and water holding capacity. Samples with a ratio of 40C: 60P enzyme concentration are wader fish protein hydrolyzate with the proportion of 40% calotropin enzyme and 60% papain enzyme is the highest sample that has an antioxidant activity of 36.41%, reduced power value of 0.57, hydrolysis degree of 74.40% and total amino acids of 82.79%. Wader fish hydrolyzate in the 70C: 30P sample of 76.98% has a high water holding capacity because it can maintain the protein component in meat. Keywords: antioxidant, calotropin, common barb fish, fish protein hydrolyzate, papain